2011
DOI: 10.1029/2010jb008120
|View full text |Cite
|
Sign up to set email alerts
|

Failure behavior of single sand grains: Theory versus experiment

Abstract: [1] Grain-scale brittle fracture and grain rearrangement play an important role in controlling the compaction behavior of reservoir rocks during the early stages of burial. Therefore, the understanding of single-grain failure is important. We performed constant displacement rate crushing tests carried out on selected, well-rounded, single sand grains and on randomly sampled grains from different grain size (d) batches of pure quartz sand. Applying a Hertzian fracture mechanics model for grain crushing, the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 69 publications
5
63
0
Order By: Relevance
“…6a, 7a and 8c, d) in agreement with the previous scanning electron microscope analyses of Tondi et al (2006). Further detailed FESEM analyses within a CSB with negligible amount of cataclasis, allowed us to documented tiny (>100 mm, not discernible under optical microscope) Hertzian cracks (Zhang et al, 1990;Brzesowsky et al, 2011) at the grain contacts (Fig. 8 aeb).…”
Section: Microstructural Observationssupporting
confidence: 72%
See 2 more Smart Citations
“…6a, 7a and 8c, d) in agreement with the previous scanning electron microscope analyses of Tondi et al (2006). Further detailed FESEM analyses within a CSB with negligible amount of cataclasis, allowed us to documented tiny (>100 mm, not discernible under optical microscope) Hertzian cracks (Zhang et al, 1990;Brzesowsky et al, 2011) at the grain contacts (Fig. 8 aeb).…”
Section: Microstructural Observationssupporting
confidence: 72%
“…As shown in Fig. 18, at low confining pressures, the cracks form either at the grain contacts (Hertzian cracks, Zhang et al, 1990;Brzesowsky et al, 2011) or, alternatively, in the proximity of slip surface (Wing cracks, Ashby and Sammis, 1990). These two typologies of cracks are characterized by different preferential orientation of propagation with respected to s 1 .…”
Section: Micromechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alonso et al, 2012). On the other hand, the experimental evidence is ambiguous: some studies (Tsoungui et al, 1999b;McDowell & Amon, 2000;Lobo-Guerrero & Vallejo, 2006) have found that the same value of the Weibull modulus is able to fit both the variability at a given scale and the variability across scales, yet others (Jansen & Stoyan, 2000;Lim et al, 2004;Brzesowsky et al, 2011) obtain the opposite result.…”
Section: Particle Failurementioning
confidence: 84%
“…b in equation (2)), this is not always accompanied by any normal compression results (e.g. Bolton et al, 1991;Lobo-Guerrero & Vallejo, 2006;Brzesowsky et al, 2011).…”
Section: Introductionmentioning
confidence: 99%